PELATIHAN PENANGANAN CEDERA KEPADA PESERTA DIDIK KELAS V DI MI DARUL HUDA DESA CODO KECAMATAN WAJAK KABUPATEN MALANG - Dio Alief Eka Utama Putra; M. Resa Anggra Kusuma (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
Real Work Lecture (KKN) is one of the courses programmed for Malang State University (UM) Students. In the implementation of the KKN program in Codo Village, the program chosen was "Training in Injury Management for Class V Students at MI Darul Huda". This program was chosen because most students like to exercise. The steps in implementing the Injury Handling Training program for Class V Students at MI Darul Huda Ds. Codo Kec. Wajak Kab. Malang are as follows: (1) observation to MI Darul Huda Codo, Wajak District, Malang Regency; (2) planning programs; (3) consulting and coordinating programs with schools; (4) determining the time and place of implementation; (5) forming an implementing committee; (6) preparation for the implementation of activities; and (7) the implementation of the KKN program. The results of the implementation of the program/activity of the Injury Handling Training activities for Class V Students at MI Darul Huda Ds. Codo Kec. Wajak Kab. Malang is very satisfying because 85% of the expected results have been achieved. From the results of the implementation which reached 85%, of course there were supporting factors that facilitated the running of the program, namely the principal who welcomed the activities to be carried out and also the sports teacher who was very enthusiastic. Apart from that, the students are also willing to help with the implementation of the activity so that they can experience the process of making the field and later use the field.